2011
DOI: 10.1080/20786204.2011.10874062
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infections among patients attending the General Practice Clinic, Wesley Guild Hospital, Ilesa, Nigeria

Abstract: S Afr Fam Pract 2011;53(1):63-70Background: Sexually transmitted infections (STIs) are among the most common infectious diseases in the world today. There are few reliable statistics on the true prevalence of STIs in developing countries, especially in the general practice setting, hence the need to determine the prevalence in each locality. With the scourge and pandemicity of human immunodeficiency virus (HIV) and the fact that STIs are recognised as independent risk factors for its transmission, determining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(39 reference statements)
1
2
0
Order By: Relevance
“…[35] An earlier age of coitarche is likely to lead to an increased in the number of lifetime sexual partners and thus an increased probability of acquisition of sexually transmitted infections. [36] In keeping with this hypothesis, our study demonstrated a significant positive relationship between Trichomonas vaginalis infection and increased number of lifetime sexual partners.…”
Section: Discussionsupporting
confidence: 83%
“…[35] An earlier age of coitarche is likely to lead to an increased in the number of lifetime sexual partners and thus an increased probability of acquisition of sexually transmitted infections. [36] In keeping with this hypothesis, our study demonstrated a significant positive relationship between Trichomonas vaginalis infection and increased number of lifetime sexual partners.…”
Section: Discussionsupporting
confidence: 83%
“…This prevalence of high-risk sexual behavior was much lower than that reported in study among other high-risk groups. [ 14 15 16 17 ] Regarding the high-risk sexual behavior, although on univariate analysis, unmarried/divorced/widow/separated marital status, unemployment status, and homosexual/bisexual sexual preference were found to be more associated with nonuse of condom during intercourse. However, logistic model revealed unemployment status and unmarried/divorced/widow/separated marital status to be significantly and independently associated with high-risk sexual behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The consequence has been sustained STI epidemics with increased spread of HIV/AIDS, leading to huge personal and economic loss. A number of studies (Olakolu et al, 2011; Isiaka-Lawal et al,2014; Oyewole et al, 2010) carried out in Western Nigeria have shown a strong relationship between the presence of other STIs and the easy transmission and high infectivity of HIV, which could be a consequence of delay in seeking care or not seeking care at all. In a country where healthcare seeking remains ahighly complex and poorly understood subject even more so where competing systems of traditional, informal and western medicine coexist (Mmari et al, 2010), efforts need to be made to provide empirical evidence to ease understanding which has practical and scientific relevance for the effective control of STIs.…”
Section: Introductionmentioning
confidence: 99%